Village level livestock and poultry production under the industrialization scenario - Rajaganapathy V (Department of Livestock Production Management, College of Veterinary and Animal Sciences, 2007)
An in depth assessment and analysis of two villages, one an industrial area and the other an agrarian hamlet, was taken up. The effect of industrialization and pollution in village level livestock and poultry production and toxic heavy metals content as an indicator of pollution in water, soil, fodder and in biological samples were studied. Based on the observation and scientific validations, changes in livestock farming system and methodologies to alleviate the extent of pollution were sorted out. This study was conducted in Plachimada village - industrial area - in Perumatty Panchayat and in Nallepilly village- control area in Nallepilly Panchayat in Chittoor taluk in Palakkad district. A detailed survey of the existing husbandry systems was done in the selected study area using a schedule. Collection of samples of water, soil, fodder and biological samples milk, meat, egg, blood and dung samples were collected and examined from both industrial and control area. The samples were analyzed for presence of heavy metals like copper, cadmium, lead and arsenic by using Atomic absorption spectrophotometer. A detailed survey was done among fifty farmers from the Plachimada (industrial area) and Nallepilly (control area) villages respectively. The farmers were interviewed with a schedule and the data was obtained. The socio-economic status of the farmers indicated that the middle aged persons were more involved in the agricultural and animal husbandry activities. Most of the farmers had an average monthly income per family of Rs. 2000 in the study area. Cultivation of crops and plantations were less in both industrial and control area. The study revealed that majority of the farmers possessed dairy cattle with major source of income from livestock farming in both these study areas. Economic viability of rearing cattle was better in control area than that of industrial area. Most of the farmers surveyed stayed very near to the industry in the industrial zone. The study revealed that nearness of the industry to the grazing lands may be affecting their livestock farming system. The presence of heavy metals cadmium and lead in drinking water and soil samples of industrial area was more than that of the control zone and the WHO (1995) recommendations. The presence of copper and cadmium in meat samples was higher whereas cadmium and lead in blood samples of the industrial area was found more than that of the control zone and the permitted levels as per the WHO recommendations. The level of copper, cadmium and lead in fodder, milk, egg and dung samples of the industrial area was found more than that of the control zone and the permitted levels as per the WHO recommendations. This study aimed also to find out the relationship between water, soil, plant and animal system. Correlation of fodder and blood heavy metals with other biological samples was done in industrial area. Fodder lead showed a highly significant correlation with milk lead content. Correlation between fodder arsenic and milk arsenic concentration was also significant. Correlation between fodder cadmium with blood cadmium was significant. Correlation was observed between fodder lead with dung lead values. Correlation existed between blood copper with dung copper at a significant level. Similarly correlation of fodder and blood heavy metals with other biological samples was done in control area also. Blood and fodder cadmium was significant and positively correlated. Correlation of fodder lead with milk and dung lead were significant. Fodder arsenic and milk arsenic were significantly correlated. In blood the copper content of milk and dung showed a positive significant correlation. The heavy metals lead, cadmium, arsenic and mercury from industrial pollution are of high environmental concern due to their toxicity even at low concentrations. These metals may persist in the system for several days due to cumulative nature and may cause severe health effects in man and animals. Bioaccumulation of toxic heavy metals, especially lead, cadmium and arsenic in milk, meat and in egg have evoked great concern during the recent years. Heavy metals contaminants may enter the animal system through pollution of air, water, soil, feed polluted by industrial sources. From the present study it was found that the industrial area had contaminated water, soil, and fodder under observation. The heavy metal contamination was from copper, cadmium and lead whereas arsenic was almost within the permissible limits. The biological samples milk, meat, egg, blood and dung collected from the industrial zone were also contaminated with copper, cadmium and lead when compared with the control area samples. The level of heavy metals in the biological samples of industrial area was above the WHO permissible limits. Arsenic was present within the maximum permissible level in all the biological samples. It is also concluded that industrialization may add pollutants to the area thereby causing an indirect effect on livestock production systems and in turn to the human beings. The following recommendations may be suggested. 1. Monitoring the level of pollution in water, soil, plants and fodder crops, animals and in man in industrial zones at regular intervals. 2. Treatment of waste water and other discharges/effluents from industries with implementation of strict rules and regulations 3. Safe disposal of the discharges, effluents and waste materials from the industries and factories. Efficient waste management to be adopted. 4. To create awareness among farming community to adopt better management practices. 5. Encouragement of organic farming. 6. Recommendation of rearing indigenous animals and adoption of Mixed farming - system to improve economic status of farmers. 7. Phytoremediation may be done to decontaminate soil and water to reduce the soil heavy metal content. 8. Identify and growing of trees/ plants to reduce the level of toxic elements from the industrial zones.